1991
DOI: 10.4319/lo.1991.36.2.0279
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐shelf transport causes recruitment to intertidal populations in central California

Abstract: The control of recruitment to intertidal barnacle populations along the central California coast was examined from April to mid-October 1988. Four recruitment pulses occurred during periods of relaxation in alongshore winds and cessation of coastal upwelling. In each case recruitment ended when strong equatorward winds reappeared -and upwelling resumed. Data on SST, salinity, adjusted sea level, and satellite (AVHRR) images revealed alternating periods of onshore and offshore transport of the surface water lay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
228
2
3

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 245 publications
(243 citation statements)
references
References 21 publications
10
228
2
3
Order By: Relevance
“…These coastal fronts interact with alongshore current systems, and provide a means for larval dispersal to connect distant populations. Relaxation or reversals in wind stress can lead to downwelling conditions where the warmer offshore surface waters and the coastal fronts are advected back onshore, delivering entrained larval organisms to the nearshore benthic habitat (Roughgarden et al, 1988;Farrell et al, 1991). Several studies have shown that variable recruitment of coastal organisms is related to upwelling dynamics in the California region (Parrish et al, 1981;Hollowed et al, 1987;Ebert and Russell, 1988;Roughgarden et al, 1988;Larson et al, 1994;Wing et al, 1995b;Connolly et al, 2001;Broitman et al, 2005;Laidig et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These coastal fronts interact with alongshore current systems, and provide a means for larval dispersal to connect distant populations. Relaxation or reversals in wind stress can lead to downwelling conditions where the warmer offshore surface waters and the coastal fronts are advected back onshore, delivering entrained larval organisms to the nearshore benthic habitat (Roughgarden et al, 1988;Farrell et al, 1991). Several studies have shown that variable recruitment of coastal organisms is related to upwelling dynamics in the California region (Parrish et al, 1981;Hollowed et al, 1987;Ebert and Russell, 1988;Roughgarden et al, 1988;Larson et al, 1994;Wing et al, 1995b;Connolly et al, 2001;Broitman et al, 2005;Laidig et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…This is one of the most important mechanistic hypotheses relating the physical transport of pelagic larvae to the nearshore environment (Roughgarden et al, 1988;Cury and Roy, 1989;Farrell et al, 1991). In most ecological studies of invertebrate recruitment, upwelling dynamics have been examined at relatively fine spatial and temporal scales (Gaines and Bertness, 1992;Wing et al, 1995a;Mace and Morgan, 2006a), from which mechanisms of larval transport could be inferred.…”
Section: Introductionmentioning
confidence: 99%
“…Upon entering the water column, the survival of larvae is mostly affected by predation (Rumrill 1990) and the availability of food (Morgan 1995). Once the larvae are competent to settle, the physical processes necessary for their onshore displacement (Shanks 1983, Farrel et al 1991, Pineda 1991, 1999, Le Fèvre & Bourget 1992, Shanks et al 2000 interact with small-scale hydrodynamics (Eckman 1983), larval behavior (Le Fèvre & Bourget 1992), the availability of suitable substrate (Raimondi 1988, Minchinton & Scheibling 1993, and early post-settlement mortality (Gosselin & Qian 1997, Hunt & Scheibling 1997, Jarrett 2000 to result in highly variable spatial and temporal patterns in recruitment.…”
Section: Introductionmentioning
confidence: 99%
“…Previous work has documented that both barnacles and mussels recruit heavily but intermittently throughout summer in Oregon (9). Recruitment events of barnacles in California (15) and Oregon † † often follow upwelling relaxation, i.e., times when larvae are transported shoreward. Barnacles and mussels create 3D spatial structure (habitat) in rocky intertidal communities and are the primary food for many predators (16).…”
mentioning
confidence: 99%